การทำกำไรโดยปราศจากความเสี่ยงจากความไม่สอดคล้องกันระหว่างราคาหุ้นสามัญและใบสำคัญแสดงสิทธิในตลาดหลักทรัพย์แห่งประเทศไทย: Arbitrage from Inconsistency between Stock Price and Warrant Price in the Stock Exchange of Thailand - กิตติวังชัย, สุทธภา; ทวีวัฒน์, ฆนัทนันท์; ทวีวัฒน์, พิษณุวัฒน์ (Journal of Applied Economics and Management Strategy, 2014)
การศึกษาเรื่อง การทำกำไรโดยปราศจากความเสี่ยงจากความไม่สอดคล้องกันระหว่างราคาหุ้นสามัญและใบสำคัญแสดงสิทธิ มีวัตถุประสงค์เพื่อศึกษาอัตราผลตอบแทนจากการยืมหุ้นสามัญมาขายพร้อมกับซื้อใบสำคัญแสดงสิทธิก่อนหักต้นทุนการกู้ยืม และศึกษาโอกาสในการทำกำไรโดยปราศจากความเสี่ยงและกลไกการปรับเข้าสู่สมดุลผลการศึกษาพบว่า เมื่อราคาใบสำคัญแสดงสิทธิรวมกับราคาใช้สิทธิและค่าธรรมเนียมต่างๆ มีมูลค่าต่ำกว่าราคาหุ้นสามัญ นักลงทุนสามารถสร้างผลตอบแทนจากส่วนต่างของราคาทั้งสองหลักทรัพย์ได้ และถ้าอัตราผลตอบแทนมีค่าสูงกว่าต้นทุนของการยืมหุ้น นักลงทุนก็จะสามารถทำกำไรโดยปราศจากความเสี่ยงได้ โดยการยืมหุ้นสามัญจากบริษัทหลักทรัพย์หรือนักลงทุนรายย่อยนอกตลาดหลักทรัพย์มาขายพร้อมกับการซื้อใบสำคัญแสดงสิทธิของหุ้นสามัญนั้นเพื่อรอแปลงสภาพ และนำหุ้นสามัญกลับมาใช้คืนผู้ที่ยืมมาจากการเก็บรวบรวมข้อมูลทุติยภูมิราคาปิด ณ สิ้นวันของหุ้นสามัญ และใบสำคัญแสดงสิทธิบมจ.บางกอกแลนด์ พบว่าส่วนต่างระหว่างราคาของหลักทรัพย์ทั้งสองสามารถสร้างอัตราผลตอบแทนก่อนหักต้นทุนการยืมหุ้นได้มากกว่าร้อยละ 30 ต่อปีหลายวันติดต่อกัน ทำให้นักลงทุนสามารถทำกำไรโดยปราศจากความเสี่ยงได้แต่สาเหตุที่ราคาไม่สามารถปรับเข้าสู่สมดุลได้ในเวลาอันสั้นเนื่องจากการยืมหุ้นทำได้ยากและปริมาณในการยืมมีอย่างจำกัด The study of arbitrage from inconsistency between stock price and warrant price aimed to examine rate of return from short sale stock with warrant buying before cost of short sale and to study arbitrage opportunity and equilibrium price - adjusting mechanism in the Stock Exchange of Thailand. The study result showed that when warrant price and exercise price, including all fees, were less than common stock price, the investor could gain on investment from such margin between those two portfolios. In addition, when the return had higher value than cost of stock borrowing, the investor would be able to arbitrage by short sale from securities company or other investors as well as buying the stock warrant of that common stock in order to wait for converting and then buy that common stock to repay the securities company or investors. According to the collection of secondary data of closing price at the end of the day of the common stock and the stock warrant of Bangkok Land PCL., there was difference of those two portfolios prices under studied before cost of short sale at more than 30%. This showed that the investors could make arbitrage, but the study also found that the two portfolios were not able to adjust to equilibrium within a short period of time because of the difficulty and limit of short sale.